THE INTEGRATION OF WOOD CARVING SKILLS INTO TEACHING AND LEARNING OF WOOD CARVING - Archer, Thomas Brown Kow; Isaac Kwabene, Agyei; Adu-Agyem, Joe; Adom, Dickson (ARTISTIC : International Journal of Creation and Innovation, 2024)
Wood carving has been an integral part of many ethnic groups in Ghana and worldwide. Currently, Ghanaian wood carvers produce countless varieties of wooden sculptures for tourist trade or export. The wood carving business in Vakpo has provided employment for natives in the production of different wooden objects such as stools, umbrella tops, linguist staffs, walking sticks, human and animal figures/figurines,  and many more. Unlike any other wood carving industry, one of the major challenges facing Vakpo traditional wood carving is less recognition by art lovers due to scanty literature in the town and insufficient art enthusiasts in Ghana.  The study adopts a qualitative research design with a descriptive research method. The data was gathered through observations and interviews. The results indicate that wood carvers in Vakpo exhibit mastery in creativity, intricate cuts as well as finishing, and their quality wood carvings are by no means inferior to the wooden sculptures of other wood carvers from renowned towns such as Aburi, Ahwiaa, Foase, and others.